The sound of light : [large type] a novel - Sundin, Sarah (Thorndike Press large print Christian fiction series., 2023)
"When the Germans march into Denmark, Baron Henrik Ahlefeldt exchanges his nobility for anonymity, assuming a new identity so he can secretly row messages for the Danish Resistance across the waters to Sweden. American physicist Dr. Else Jensen refuses to leave Copenhagen and abandon her research--her life's dream. While printing resistance newspapers, she hears stories of the movement's legendary Havmand--the merman--and wonders if the mysterious and silent shipyard worker living in the same boardinghouse has something to hide.When the Occupation cracks down on the Danes, these two passionate people will discover if there is more power in speech . . . or in silence. Bestselling author of more than a dozen WWII novels, Sarah Sundin offers pens another story of ordinary people responding to extraordinary circumstances with faith, fortitude, and hope for a brighter future"--